Auxin autotrophic tobacco calli with modified aldehyde oxidase isoenzyme activities show enhanced abiotic stress tolerance - Csiszár Jolán (2007)
The growth, abiotic stress resistance and aldehyde oxidase (AO) activities of auxin autotrophic and heterotrophic tobacco calli were compared. The auxin-independent autotrophic calli maintained their growth rate even at 35°C temperatures, showed enhanced abiotic stress resistance in the presence of 50-300 mM NaCI, 0.1-5 mM KN02 or 0.1-10 mM H202. 0.1-5 mM H202 caused a higher increase in glutathione S-transferase (GST) and glutathione peroxidase (GPÖX) activities of heterotrophic calli, however these enzymes worked in an elevated level in autotrophic lines under control circumstances and were induced differently under oxidative stress, indicating an altered signalling mechanism. AO activity could be detected by activity staining after native PAGE with indole-3-acetaldehyde (lAAld) substrate in both calli, which means that the enzyme catalyzing the last step in IAA biosynthesis is present in both tissues. Contrary to heterotrophic calli, in the auxin autotrophic cultures an isoenzyme with low mobility (AOI) was detectable. 100 mM NaCI enhanced the AOI activity and a new isoenzyme (A02) was observed. The increase of the activities of these isoenzymes were higher in the autotrophic lines suggesting that the enhanced IAA biosynthesis can play a role in the recovery of growth under stress conditions.